2020
DOI: 10.1007/s13311-019-00776-7
|View full text |Cite
|
Sign up to set email alerts
|

Extending the Interval of Natalizumab Dosing: Is Efficacy Preserved?

Abstract: Extending the natalizumab interval after the 24th administration could reduce the risk of progressive multifocal leukoencephalopathy (PML). The objective is to evaluate the noninferiority of the efficacy of an extended interval dosing (EID) compared with the standard interval dosing (SID) of natalizumab. It is an observational, multicenter (14 Italian centers), retrospective cohort study, starting from the 24th natalizumab infusion to the loss of follow-up or 2 years after baseline. Patients were grouped in 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 33 publications
6
47
0
1
Order By: Relevance
“…This potential activity is perhaps consistent with increased lung infections in MS following treatment with natalizumab (Polman et al, 2006). Furthermore, that SARS-CoV-2 is neutrotrophic, (Baig et al, 2020;Moriguchi et al, 2020, Helms et al 2020 suggests that a potential risk of natalizumab treatment is that it blocks viral immunosurveillance of the CNS (Hoepner et al, 2014), however this issue is perhaps limited by the extended interval dosing suggested to limit MS activation and reduce the risk of progressive multifocal leukoencephalopathy (Ryerson et al, 2019;Clerico et al, 2020). Thus, whilst natalizumab use could potentially be a risk factor for severe COVID-19, it is likely to limit monocyte and T cell damage to the lung and avoiding severe complications.…”
Section: Natalizumab As the Preferred High-efficacy Agentmentioning
confidence: 86%
“…This potential activity is perhaps consistent with increased lung infections in MS following treatment with natalizumab (Polman et al, 2006). Furthermore, that SARS-CoV-2 is neutrotrophic, (Baig et al, 2020;Moriguchi et al, 2020, Helms et al 2020 suggests that a potential risk of natalizumab treatment is that it blocks viral immunosurveillance of the CNS (Hoepner et al, 2014), however this issue is perhaps limited by the extended interval dosing suggested to limit MS activation and reduce the risk of progressive multifocal leukoencephalopathy (Ryerson et al, 2019;Clerico et al, 2020). Thus, whilst natalizumab use could potentially be a risk factor for severe COVID-19, it is likely to limit monocyte and T cell damage to the lung and avoiding severe complications.…”
Section: Natalizumab As the Preferred High-efficacy Agentmentioning
confidence: 86%
“…Given the patient's positive John Cunningham (JC) virus immunoglobulin G status, we decided to administer every 8-week extended interval dosing (EID) of natalizumab, given that evidence was emerging to demonstrate that such a longer latency between treatments was not associated with a compromise in clinical or paraclinical measures of MS disease activity 7 while simultaneously mitigating the risk of progressive multifocal leukoencephalopathy (PML), when compared with standard interval dosing of every 4-week treatments. 8 , 9 The first infusion was strategically administered 1 week before inception of etanercept treatment.…”
Section: Case Presentationmentioning
confidence: 99%
“…This risk is further stratified by the quantitative index where a JCV Ab index >1.5 in patients with MS treated with natalizumab at 4-week intervals is associated with high risk of PML, 7 although data suggest that extended interval dosing confers a lower risk of PML without compromising efficacy. [8][9][10] Diagnostic confirmation of PML can often represent a formidable challenge, particularly given the heterogeneity in imaging characteristics. The conspicuity of PML lesion morphology in the context of HIV/AIDS can be distinctive from lesions evolving as a consequence of protracted immunosuppression in patients with autoimmune disorders.…”
Section: Discussionmentioning
confidence: 99%